Should boys receive the human papillomavirus vaccine? Yes. (7th December 2009) - Hibbitts, Sam
Abstract : Many countries have implemented HPV vaccination programmes for girls. Sam Hibbitts argues that they will not be fully effective unless extended to boys, but Kate Cuschieri (doi:10.1136/bmj.b4921 ) says the benefit is insufficient